2011
DOI: 10.4236/fns.2011.28114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Food Hygiene Knowledge Attitudes and Practices of Food Handlers in Food Businesses in Accra, Ghana

Abstract: Food handlers have a prime role to play in food businesses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 10 publications
8
37
2
1
Order By: Relevance
“…In this study majority of participants had studied up to secondary level which was similar to the study conducted in Malaysia, Nigerian [5]. Study conducted in Aligarh, Ethiopia, Maharashtra showed majority of participant were illiterate [1,2,3].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this study majority of participants had studied up to secondary level which was similar to the study conducted in Malaysia, Nigerian [5]. Study conducted in Aligarh, Ethiopia, Maharashtra showed majority of participant were illiterate [1,2,3].…”
Section: Discussionsupporting
confidence: 54%
“…In large scale cooking, food passes through many hands, thereby increasing the chances of food contamination due to improper handling. Deliberate or accidental contamination of food during large scale production might endanger to the health of the consumers, and have very expensive repercussion on a country [3].…”
Section: Inroductionmentioning
confidence: 99%
“…Participants having their mother house wives scored significantly higher than working women which was 36.8% and that of working women was 32%. Participants living in hostel had a better score than those living with their families which was 39% and those living with their families were 37% and those participants with age range from 23-24 years had a better knowledge about refrigeration which is 53% (Table 5) [10][11][12][13].…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%
“…Unintended contamination of food during large scale cooking, leading to foodborne disease outbreaks can pose danger to the health of consumers and economic consequence for nations [1][2][3]. Foodborne related illnesses have increased over the years, and negatively affected the health and economic well-being of many developing nations [4].…”
Section: Introductionmentioning
confidence: 99%